Assessment and management of adverse drug reactions in general medicine department: a prospective observational study - Fatima, Anam; Fatima, Masarath; Rayan, Mohammed Abrar; Tabassum, Sofiya; Begum, Syeda Zuleqaunissa (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Adverse drug reactions (ADRs) are unintended and harmful responses to medications given at normal therapeutic doses. They contribute significantly to morbidity and prolonged hospital stays, particularly in general medicine departments where polypharmacy and comorbidities are common. The study aimed to monitor, evaluate, and prevent ADRs among inpatients in the general medicine department using established pharmacovigilance tools to enhance treatment safety and effectiveness. Methods: A prospective observational study was conducted over three months in the general medicine department of a tertiary care hospital. Inpatients aged ≥18 years receiving at least one medication and consenting to participate were included. ADRs were identified through active monitoring of clinical signs and records. Each ADR was evaluated for causality (using WHO-UMC and Naranjo’s algorithm), severity (Hartwig and Siegel scale), and preventability (Schumock and Thornton scale). Results: Among 170 patients, the highest incidence of ADRs was observed in the 41-60 years group (40.6%), with females affected more than males. Hypertension (HTN) and diabetes were common comorbidities. The most frequently suspected drugs included Inj. Monocef, Inj. Levipil, and Inj. Zofer. Antibiotics and gastrointestinal medications accounted for the majority of ADRs. The majority of ADRs were moderate, probable in causality, and potentially preventable. Management involved withdrawal or dose adjustment of the suspected drug, leading to high recovery rates. Conclusions: This study emphasizes the importance of vigilant ADR monitoring in general medicine. Early detection, risk factor evaluation, and proper management significantly reduce ADR related complications. Strengthening pharmacovigilance practices can enhance patient safety and therapeutic outcomes in clinical settings.